SIMULASI PENERAPAN TEORI ANTRIAN DALAM PEMBATASAN PENGUNJUNG OBJEK WISATA - Setiawan, Ezra Putranda; Sukoco, Heru; Harini, Lusi (PATTIMURA UNIVERSITY, 2021)
Restrictions of the visitor on the tourism places is one of the mechanism of health protocol that carried out during the new normal era. This restriction become a dilemma since the manager of the tourism places want to maximize their profit by allowing all visitor, while the government still limiting the number of visitor to avoid crowding. Otherwise, real-time monitoring of the number of visitor somewhat difficult since they can come in and leave the tourism places at any time. In this study we implement the queuing theory to solve this problem. The visitor of the tourism places is modelled as the customer, while the time spent by them in the tourism places is modelled as the serving duration. By estimating the average of time spent by the visitor and determine the average number of arrivals during the specified time, the number of visitor in the tourism place can be estimated as the number of people in the queuing system. As a preliminary study, this paper only focused on two queuing model, namely the M/M/1 and M/G/1. Further study is needed to develop the model and calibrate it using the data from a specified tourism place.